Propuesta para generar lineamientos de caducidad en la acción de cobro de los intereses de mora patronal por parte del Instituto Ecuatoriano de Seguridad Social. - Sánchez Vega, Alba Lucia (2024)
This study addressed the expiration in the action for collection of interest on employer arrears by the IESS, before the discretionary power of the public administration, being affected the individual rights of the subject of the obligation, in the motivation and due reasonableness; examining that discretion is arbitrary and used to produce a deviation of power, by notifying employers in an untimely manner, which generated legal and economic effects. The objectives were verified and fulfilled with the review of literature and practical cases of the action for collection of interest on obligations generated by the employer's default, violating the rights to legal security of employers, although the law provides that, in cases of employer liability, within thirty (30) days of the occurrence of the event that determines it, the IESS should initiate the corresponding coercive lawsuit against the employer in arrears, a situation that is not met by the creditor institution of the obligation. Therefore, the qualification work had a qualitative approach, with methodology and technique in the collection of data on the review of case documents, where it can be evidenced that the IESS relied on administrative discretion to notify the employer about the payment of interest, obtaining reliable results, since the sample is part of a whole, with similar characteristics in the entity of the Executive Function, it was possible to make a classification of the factors that, in good judgment, have practically conditioned the results to be obtained. The proposal generated is that the employer should be notified of the obligation within 365 days, after the expiration of which the power to collect interest will expire, losing competence due to the time and in application of the preclusion guarantee and the legal certainty principle.